2016
DOI: 10.1007/s13277-016-5019-9
|View full text |Cite
|
Sign up to set email alerts
|

GAB2 promotes cell proliferation by activating the ERK signaling pathway in hepatocellular carcinoma

Abstract: Grb2-associated binding protein 2 (GAB2), a key member of the family of Gab scaffolding adaptors, is important in the phospoinositide3-kinase (PI3K) and extracellular signal-regulated kinase (ERK) signaling pathways, and is closely associated with cell proliferation, cell transformation, and tumor progression. But its role in hepatocellular carcinoma (HCC) is still unknown. In this study, we investigated the expression of GAB2 and its potential clinical and biological significances in HCC. Western bolt and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
1
22
0
1
Order By: Relevance
“…These findings indicate that Gab2 might be a tumor-associated protein. Two recent studies investigated Gab2 expression in HCC samples and confirm our results (26, 27). Gab2 is also associated with tumor behavior in other types of malignancies, such as breast cancer (28), melanoma (29), ovarian cancer (30), lung cancer (31), glioma (32), and gastric cancer (33).…”
Section: Discussionsupporting
confidence: 88%
“…These findings indicate that Gab2 might be a tumor-associated protein. Two recent studies investigated Gab2 expression in HCC samples and confirm our results (26, 27). Gab2 is also associated with tumor behavior in other types of malignancies, such as breast cancer (28), melanoma (29), ovarian cancer (30), lung cancer (31), glioma (32), and gastric cancer (33).…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, it has previously been shown to function as a proto-oncogene within melanoma, hepatocellular carcinoma, and breast, colorectal, and ovarian cancers. [49][50][51] Although the association with rs948662 that exceeded the multiple-testing correction threshold was for overall GCT risk, we observed increased point estimates of similar magnitude and nominal associations for this variant and ovarian and intracranial tumors and germinomas.…”
Section: Discussionmentioning
confidence: 61%
“…It has been previously reported that aberrant Gab2 signaling is associated with human tumorigenesis [2931]. Gab2 is involved in many cancerous behaviors, including cellular growth, survival, proliferation, and migration [2831].…”
Section: Discussionmentioning
confidence: 99%
“…siRNA sequences for human Gab2 were combination of 5-CCTGAATGTGT GCCTTAAA-3, and 5-GCCAACTCTGTTCACGTTT-3 [29]. Gab2 siRNAs were synthesized by Genechem (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%